Pemanfaatan Kompos Limbah Pertanian Dalam Budidaya Kacang Tanah di Kecamatan Kediri Lombok Barat - Silawibawa, I Putu; Mulyati, Mulyati; Sutriono, Raden; Susilowati, Lolita Endang; Arifin, Zaenal; Fahrudin, Fahrudin (Jurnal Gema Ngabdi, 2022)
Peanuts are the fourth staple food after rice, corn and soybeans. This is due to the high nutritional content, including rich in fat, protein, carbohydrates, vitamins and minerals. Peanut seeds have a high economic value, because they can be used as a variety of food industry products, such as pecel and satay seasonings, bread, and various processed raw peanuts, such as salted peanuts, atomic beans, and other seasoned nuts.The need for peanuts from year to year continues to increase, but the production is still very low, thus triggering the high price of this commodity in the market. The low production of peanuts is due to the lack of application of cultivation techniques and the lack of use of fertilizers. This Community Service aims to increase peanut production by applying appropriate cultivation techniques, utilizing agricultural waste compost and providing understanding to farmers about the importance of fertilizing peanut plants. Based on community service activities, it can be concluded that the utilization of agricultural waste compost in peanut cultivation in Kediri District, West Lombok Regency, is considered successful. This can be seen from the response of farmers in participating in community service activities, both in discussions and in paying attention to plot demonstration activities in the field.